2013
DOI: 10.5194/hess-17-2529-2013
|View full text |Cite
|
Sign up to set email alerts
|

Variation in turbidity with precipitation and flow in a regulated river system – river Göta Älv, SW Sweden

Abstract: Abstract. The turbidity variation in time and space is investigated in the downstream stretch of the river GötaÄlv in Sweden. The river is heavily regulated and carries the discharge from the largest fresh water lake in Sweden, Lake Vänern, to the outflow point in Göteborg Harbour on the Swedish west coast. The river is an important waterway and serves as a fresh-water supply for 700 000 users. Turbidity is utilised as a water quality indicator to ensure sufficient quality of the intake water to the treatment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 42 publications
(24 reference statements)
3
23
0
Order By: Relevance
“…In this paper, two forms of AAP, namely the antecedent AAP and the cumulative antecedent AAP, were considered when investigating the associations of flow and water quality with precipitation, as these two precipitation metrics have been often used in the literature [12][13][14][15][16]. The antecedent AAP is the AAP on a designated antecedent day, while the cumulative antecedent AAP is the sum of AAPs from the current day to a designated antecedent day.…”
Section: Water Quality Flow and Precipitation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, two forms of AAP, namely the antecedent AAP and the cumulative antecedent AAP, were considered when investigating the associations of flow and water quality with precipitation, as these two precipitation metrics have been often used in the literature [12][13][14][15][16]. The antecedent AAP is the AAP on a designated antecedent day, while the cumulative antecedent AAP is the sum of AAPs from the current day to a designated antecedent day.…”
Section: Water Quality Flow and Precipitation Datamentioning
confidence: 99%
“…Precipitation, which produces surface runoff, undoubtedly affects water quantity and consequently water quality indirectly. Many studies have demonstrated the increase of concentrations and/or loadings of various pollutants including total suspended solids (TSS), nutrients, and microorganisms (e.g., E. coli and pathogens) during storm events and extensive rainfalls [12][13][14][15][16]. The linkage between water quality and precipitation is more prominent in heavy rainfalls.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy rainfall is a common cause for increased turbidity and raising the water level, such as FS2. Göransson, Larson and Bendz (2013) found a positive correlation between turbidity and rainfall in periods with heavy rainfall.…”
Section: Turbiditymentioning
confidence: 92%
“…Generally, the suspended sediment load carried by the rivers during the rainy season is higher than that found during the dry season (Dunlop et al, 2008;Göransson et al, 2013); however, in regulated river systems, seasonal variations in load do not always follow such a trend (Göransson et al, 2013). Shear forces are also seasonally variable, since these forces are a function of the water level (Hubbs, 2006b).…”
Section: Clogging and Self-cleansing In Rbfmentioning
confidence: 99%